If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 29 = x + 28 Reorder the terms: 29 + 2x = x + 28 Reorder the terms: 29 + 2x = 28 + x Solving 29 + 2x = 28 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 29 + 2x + -1x = 28 + x + -1x Combine like terms: 2x + -1x = 1x 29 + 1x = 28 + x + -1x Combine like terms: x + -1x = 0 29 + 1x = 28 + 0 29 + 1x = 28 Add '-29' to each side of the equation. 29 + -29 + 1x = 28 + -29 Combine like terms: 29 + -29 = 0 0 + 1x = 28 + -29 1x = 28 + -29 Combine like terms: 28 + -29 = -1 1x = -1 Divide each side by '1'. x = -1 Simplifying x = -1
| x^2-12X+C=Y | | a^2+5a=5a+4 | | 6b+9=122 | | Sec^2x-4secx=-4 | | 8t^2-5t-3=h | | -15=-7y+5(y-5) | | 5y-8=65 | | 2x+8=5+x | | c^2=8c-16 | | 0.1q-2r= | | 4x-2(4x+9)=14 | | 5x+34+4=30 | | 3x+2+77=180 | | 2x+6-3(x-1)=2 | | 6b+9=123 | | 3(4+66)=25 | | 0.1-2r= | | Y=(2y)-2 | | 7=1515+10x | | T-1/3=4/t | | -28-2m=20 | | 4u+3u=14 | | -7x+2(3x-11)=-27 | | 3u+4u=13 | | 3x+(-x+0)=-8 | | (2/5)^-3 | | -1.5(x+3.2)+5=3x-(8.8) | | X^2-121/3x^2-9x | | 3x+2y+4x+y= | | x^2-4kx+3+k=0 | | 2x-7(4x-3)=-109 | | -3(2p+7)-14=-2(p+8)+5 |